Analisis Pengaruh NPF, CAR, dan FDR terhadap Profitabilitas Bank Umum Syariah di Indonesia Periode 2015-2019 - Chika Damayanti; Ade Ali Nurdin; Rochmi Widayanti (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to analyze the effect of Non Performing Financing, Capital Adequacy Ratio and Financing to Deposit Ratio on the profitability of Indonesia’s Islamic Banks for the period 2015-2019 which is proxied by Return on Asset. The data in this study were obtained from Islamic Banking Statistics that published by Indonesia Financial Services Authority (OJK) from January 2015 until December 2019 with a total of 60 data. The method used is multiple linear regression analysis and the results shows that Non Performing Financing has a significant negative effect on Rerturn On Aasset, Capital Adequacy Ratio has a significant positive effect on Return On Asset and Financing to Deposit Ratio does not have a significant effect on Return On Asset.